Customer experience requirements for e-commerce websites. (9th July 2007) - De Bruijn, Oscar; De Angeli, Antonella; Sutcliffe, Alistair
With the emergence of highly interactive applications on the World Wide Web has come a realisation that customer engagement is an increasingly important requirements consideration. It is currently not clear, however, what kinds of requirements websites have to adhere to in order to offer the right kinds of customer experience. In this paper, we report on a study in which we explored the relationships between content, presentation and usability of websites and how these relate to the overall satisfaction of the user and their willingness to purchase goods and services. Based on the results we can make recommendations about requirements considerations for content and presentation in the form of trade-offs that need to be considered by requirements-engineers.